1972
DOI: 10.2466/pr0.1972.31.1.119
|View full text |Cite
|
Sign up to set email alerts
|

Blinking and Mental Load

Abstract: The rate of blinking is related to certain mental activities. One common feature of states associated with low blink rates is the presence of concentrated cognitive activity. The purpose of the present study was to determine how blinking is affected by variations in mental load; it was hypothesized that, for a given nonvisual task, blinking would decrease as mental load increased. The first study reported here manipulated memory load by requiring Ss to retain a sequence of 4, 6, or 8 digits. The second study i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
58
0
1

Year Published

1973
1973
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(68 citation statements)
references
References 10 publications
7
58
0
1
Order By: Relevance
“…The only AU which showed both a significant and consistent correlation (though not necessarily in the top 3) with difficulty was AU 45 (blink) -for 6 out of 8 subjects their difficulty labels were negatively correlated with blink, meaning these subjects blinked less during the more difficult sections of video. This finding is consistent with evidence from experimental psychology that blink rate decreases when interest or mental load is high [13,14]. To our surprise, AU 4 (brow lowerer), which is associated with concentration and consternation, was not consistently positively correlated with difficulty.…”
Section: Resultssupporting
confidence: 81%
“…The only AU which showed both a significant and consistent correlation (though not necessarily in the top 3) with difficulty was AU 45 (blink) -for 6 out of 8 subjects their difficulty labels were negatively correlated with blink, meaning these subjects blinked less during the more difficult sections of video. This finding is consistent with evidence from experimental psychology that blink rate decreases when interest or mental load is high [13,14]. To our surprise, AU 4 (brow lowerer), which is associated with concentration and consternation, was not consistently positively correlated with difficulty.…”
Section: Resultssupporting
confidence: 81%
“…Another research has measured the blink rate in resting, reading and talking conditions [1]. A few studies have examined blink features in two cognitive load levels and found them related with mental load level [5,8].…”
Section: Introductionmentioning
confidence: 99%
“…For example, anxiety is associated with high blink rates and intense cognitive activity with low blink rates. Holland and Tarlow (1972) similarly report differential rates of blinking for different mental states. Hall (1945) conducted a series of experiments on eye blinks, and he discussed the variety and purposes of blinks in man.…”
Section: Faril Yn Jones and Larry Hochhausmentioning
confidence: 95%